Measurement of LLE For Biodiesel and Bio-Oil in Solvents - Zulkefli, Ahmad Umair (Universiti Teknologi PETRONAS, 2011)
Biodiesel is an alternative fuel for internal combustion engmes. It can reduce carbon monoxide (CO), hydrocarbon (HC) and particulate matter (PM) emissions, compared with diesel fuel, but there is also an increase in nitrogen oxides (NOx) emission. The combustion of diesel oil will produces carbon dioxide that contribute to global warming and sulfur that lead to acid rains. Furthermore, the high prices of fossil fuel make researchers find an alternative and renewable fuel. The diesel oil or methyl ester is produced in transesterification oftriglycerides with methanol. It is called in other name with alcoholysis. In the reaction of producing biodiesel, the product that is glycerol is formed simultaneously to methyl esters. This condition will complicate the reactant and product recovery and thus increase operation cost. The knowledge of the complex phase behaviours is essential in designing and optimizing the recovery. Therefore, an experimental investigation of the complex phase behaviours between methanol, different oils, and catalyst as reactants and methyl ester and glycerol as products need to be done to define suitable process conditions for reaction and product separation. Hopefully this study will enhance the production of biodiesel from rubber seed oil m Malaysia.